ANALYSIS OF STUNTING INCIDENTS IN TODDLER CHILDREN AT THE MUSI RAWAS REGENCY HEALTH CENTER - Nadya Assagaf, Syarifah; Ali Harokan; Arie Wahyudi (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Children who experience malnutrition, repeated infections, and inadequate psychosocial stimulation can result in impaired growth and development or stunting. There are still findings of cases of stunting in children under five, followed by the presence of malnourished children under five, where in 2023 there will be 243 stunting. There are many factors that cause stunting in the Puskesmas work area which causes problems in children, both health and growth and development. This research aims to determine the factors which is related to the incidence of stunting in children under five at the Megang Sakti Community Health Center, Musi Rawas Regency in 2024. The design of this research is quantitative research with a cross-sectional approach. The population in this study is the target group of children under five in 2023, totaling 32,561 respondents. The sample in this study consisted of 100 respondents. The sampling method uses purposive sampling technique, using the Slovin formula. Inclusion criteria are willingness to become a respondent by filling out a consent form. This research was carried out on March 10 - April 30 2024 at the Megang Hospital Health Center. Collecting primary data by interviews using questionnaires. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. The results of the study showed that there was a relationship between maternal age (p value 0.02) and birth weight (p value 0.002) with the incidence of stunting in children under five at the Megang Sakti Community Health Center, Musi Rawas Regency. in 2024. The conclusion is that there is a relationship between age and birth weight with the incidence of stunting in children under five at the Megang Sakti Community Health Center, Musi Rawas Regency in 2024. The community health center should carry out continuous screening of children under five who are at risk of stunting and provide education on efforts to prevent stunting children, such as risk factors for stunting.